VARIATIONS OF SEA LEVEL AND SEA SURFACE TEMPERATURE IN THE CALDERA OF SANTORINI ISLAND , SOUTHERN AEGEAN SEA - Albanakis, K.; Styllas, M.; Yfantis, V. (Bulletin of the Geological Society of Greece, 2018)
Analyses of sea level records within the Caldera of Santorini Island revealed the significance of both océanographie and atmospheric forcing on the observed signals. Sea level (msl) and sea surface temperature (sst) data were obtained from the four stations of the REMOS monitoring network. Out of the four stations Gialos station is located on the caldera whereas the remaining three (Erinia, Taxiarhis and Agios Nikolaos) are located on the young volcanic islands of Palaia and Nea Kameni. The record of sea level data contained a number of gaps. When possible, (i.e. small gaps) missing values were estimated with linear interpolation. Harmonic analysis on continuous parts of the record revealed a mixed type of tide with similar Nf values for the four stations, a result of their locations being close to each other. No co-oscillation phenomena were found within the caldera. Sea level at Taxiarhis station is affected more by atmospheric forcing and shallow water effects in contrast with Gialos station where mean sea level displays significant correlation (r=0.62) with sea surface temperature at lags 2-6 days. The annual cycle of mean sea level (amplitude=5.74cm) responds to seasonal variations in the thermal structure of the waters, and together with the semiannual cycle explains 9.02% of the variance in the annual frequency band. Existing data are not sufficiently long to develop a model, which will reconstruct sea level variability resulting from océanographie and meteorological forcing and will be used for the detection of ground movements from future volcanic eruptions.